SOSIALITAS YANG TERUKUR MAHASISWA BERDASARKAN PRESENTASI DIRI DI DUA AKUN INSTAGRAM: Studi Fenomenologi dua akun Instagram pada Mahasiswa IAI AL-AZIS - Nahniya Isnain Septiorini; Muhammad Nurkholis Abdurrazaq; Elang Bakhrudin H (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study explores student self-presentation on Instagram, focusing on the use of public and private accounts within the context of digital sociality. Employing a qualitative phenomenological approach, data were collected through in-depth interviews, and observations of seven students. Michikyan’s Self-Presentation theory and Miller’s concept of Scalable Sociality were used as analytical frameworks to examine how students balance the True Self, Ideal Self, and False Self by scaling their interactions from intimate audiences to public ones. The findings reveal that public accounts are utilized to project the Ideal Self through aspirational content, whereas private accounts serve as spaces for the authentic expression of the True Self. In the context of Muslim students, Islamic ethics, based on the Hadith concerning the responsibility of leadership (Sahih Bukhari: 2278) and Surah As-Saff [61]: 2–3, influence content choices aimed at maintaining moral integrity. This research introduces the concept of the Hybrid Self, which reflects an integration of authenticity and aspiration, and highlights Instagram’s role as a reflective tool. The study contributes to the understanding of digital sociality and offers recommendations for digital literacy within educational institutions.